Effects of Date Seed Coffee as a Complementary Therapy on Blood Pressure Among Hypertensive Patients at Kartini General Hospital - Lisdiana; Dewi Woro Astuti; Hidayatusy Syukrina Puteri (CV. CENDIKIA JENIUS INDONESIA, 2026)
Hypertension is a very serious health problem worldwide. A person is said to have hypertension if his systolic blood pressure reaches 140 mmHg or more, and his diastolic blood pressure is 90 mmHg or more. One of the alternatives that is developing in the world of herbal medicine is the use of date seeds, one of which is date seed coffee which has the potential to be a complementary therapy for various degenerative diseases, such as hypertension. This study aims to determine the effect of giving date seed coffee on blood pressure in hypertensive patients.The method used in this study is quantitative using a quasi-experiment design with a sample of 20 respondents. Data will be collected through surveys or observation sheets, and analyzed using appropriate statistical methods such as the paired t test.The results of the study showed the effect of giving date seed coffee on blood pressure in hypertensive patients with a p value of 0.000 < 0.05. The results of this study are expected to make date seed coffee one of the safe, cheap, and practical alternatives to hypertension treatment. Hypertensive patients must also regularly consume antihypertensive drugs and consume nutritious foods to maintain heart health and blood pressure.